Hypercalcemia of Malignancy - Feldenzer, Kaitlin L. (J Adv Pract Oncol, 2018)
Hypercalcemia of malignancy (HCM) is a common concern in patients being treated for cancer, affecting over a quarter of this population. There are multiple causes of HCM, including humoral HCM, osteolytic HCM, ectopic hyperparathyroidism, and vitamin D–secreting lymphomas. Common signs and symptoms of HCM can range from mild gastrointestinal disturbances and fatigue to seizures, coma, or even cardiac arrest depending on the severity of the laboratory abnormality. Treatment has evolved in recent years and varies based on the underlying cause of the HCM. Management options include aggressive hydration, bisphosphonates, denosumab, calcitonin, and corticosteroids. It is imperative that advanced practitioners understand the pathophysiology behind the HCM so that proper treatment can be chosen. Early and appropriate treatment is key to successful outcomes. It is also important for continuous monitoring to occur alongside treatment for HCM to prevent potential adverse effects. Finally, the ultimate resolution of HCM comes only from the treatment of the underlying malignancy; therefore, all previously undiagnosed patients should be referred to an oncologist early after HCM is recognized.